Letter to Jane Tolmach; from George Grimes - George Grimes:::::: (1964)
Letter to Jane Tolmach, from George Grimes (Chairman & Board of Trustees) sent on January 8, 1964. George Grimes sent an invitation for a lunch meeting to occur on January 18, 1964, and was seeking for approval from all Trustees of Camarillo State Hospital.